Human B Cells Mediate Innate Anti-Cancer Cytotoxicity Through Concurrent Engagement of Multiple TNF Superfamily Ligands - Janjic, Bratislav M.; Kulkarni, Aditi; Ferris, Robert L.; Vujanovic, Lazar; Vujanovic, Nikola L. (Frontiers in Immunology, 2022)
The essential innate immunity effector cells, natural killer and dendritic cells, express multiple plasma membrane-associated tumor necrosis factor (TNF) superfamily (TNFSF) ligands that, through simultaneous and synergistic engagement, mediate anti-cancer cytotoxicity. Here, we report that circulating B cells, mediators of adaptive humoral immunity, also mediate this innate anti-cancer immune mechanism. We show that resting human B cells isolated from peripheral blood induce apoptosis of, and efficiently kill a large variety of leukemia and solid tumor cell types. Single-cell RNA sequencing analyses indicate, and flow cytometry data confirm that B cells from circulation express transmembrane TNF, Fas ligand (FasL), lymphotoxin (LT) α1β2 and TNF-related apoptosis-inducing ligand (TRAIL). The B cell cytotoxic activity can be inhibited by individual and, especially, combined blockade of the four transmembrane TNFSF ligands. B cells from tumor-bearing head and neck squamous cell carcinoma patients express lower levels of TNFSF ligands and are less cytotoxic than those isolated from healthy individuals. In conclusion, we demonstrate that B cells have the innate capacity to mediate anti-cancer cytotoxicity through concurrent activity of multiple plasma membrane-associated TNFSF ligands, that this mechanism is deficient in cancer patients and that it may be part of a general cancer immunosurveillance mechanism.